Governance, culture, and legacy of Melaka on shaping Malaysia's nation building - Mat, Zawiah; Che Husain, Faridah; Halim, Harliana; Muhammad Akbar, Waqar; Abdullah, Mohd Syariefudin (Research and Scientific Innovation Society, 2025)
The Malay Sultanate of Melaka represents a pivotal foundation in Malaysia's historical trajectory of nation building. This study examines the political, cultural, and economic legacies of the Sultanate and their enduring influence on the development of national identity, governance structures, and socio-cultural integration in modern Malaysia. The method used for this research is qualitative descriptive by analysis of existing historical manuscripts, government archives, scholarly books, academic journals, and reputable online databases. Document analysis involves a systematic review of written records to identify key themes related to nation building. This study highlights how Melaka’s history, cultural assimilation, political system, trade, religious values, and language have shaped Malaysia’s pluralistic society. The analysis emphasizes the Sultanate's role as a catalyst for regional unity and a governance model that influenced later political traditions. Ultimately, Melaka’s legacy is essential for understanding Malaysia’s contemporary nation-building framework.